Design of Fruit Fly Trap ApelB Using a Microcontroller and Sensor System Powered by Solar Photovoltaic - Masrur Alatas; Mohammad Syamsul Arifin; Dimas Taufiq Ridlo; Ucik Ika Fenti Styana (The University of Lampung, 2025)
Indonesia’s vast horticultural land faces serious threats from Bactrocera fruit fly infestations, a type of fruit fly in the Tephritidae family that causes rotting plants, reducing the quality of plantation and agricultural products, and even crop failure. The purpose of this study was to design a fruit fly (Bactrocera) trap ApelB version 1.1, using the Cockcroft-Walten Circuit, Methyl Eugenol, PIR HC-SR501 sensor, Arduino Uno ATmega328P, powered by electricity from a Solar Power Plant/System (PLTS) with a panel capacity of 10 Wp, Solar Charge Controller 10 A and a 14.8 V 2.5 Ah battery. The ApelB version 1.1 test method on agricultural land for 24 hours used methyl eugenol to attract fruit flies to enter the trap. Electricity from the PLTS functions to eradicate fruit flies that land on the electric net trap. The findings of ApelB version 1.1 successfully attracted, detected through sensors, and eradicated fruit flies with electric shocks. The capture rate was 80% in lab tests, while corn and chili field trials caught an average of 148–150 fruit flies. ApelB version 1.1 can suppress attacks and fruit fly populations, with a PLTS system and energy storage battery. This tool is guaranteed to operate 24 hours automatically.